The pedagogical training of the teacher in the Nursing Career exercise. An essential necessity of the ecuadorian university - Piedra Chávez, Ketty; Baute Álvarez, Luisa (Revista Universidad de Guayaquil, 2016)
This paper aims to reflect on the need for the pedagogical formation of teachers in exercise of the Nursing Career in Ecuador. Such reflection is based on a study on continuous formation in Ecuadorian universities, which throws the existence of few experiences on teacher training. The relevance of the exhibition is that the teachers working are heterogeneous. And on the other in their professional formation were not prepared for the exercise of teaching. The methodology is essentially qualitative, based on the study of scientific and legislative existing documentation and the implementation of methods that provide relevant information about the real state of the problem and the need for its transformation through alternatives of pedagogical formation